2003
DOI: 10.1016/s0140-9883(02)00099-3
|View full text |Cite
|
Sign up to set email alerts
|

Do oil price shocks matter? Evidence for some European countries

Abstract: This paper analyzes the oil price-macroeconomy relationship by means of analyzing the impact of oil prices on inflation and industrial production indexes for many European countries using quarterly data for the period 1960-1999. First, we test for cointegration allowing for structural breaks among the variables. Second, and in order to account for the possible non-linear relationships, we use different transformation of oil price data. The main results suggest that oil prices have permanent effects on inflatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(179 citation statements)
references
References 26 publications
7
151
1
7
Order By: Relevance
“…8 We find an impact on consumer prices which is relatively strong for all energy-importing countries except for Japan, whereas inflationary pressures are negligible or even negative in net energy-exporting countries (see also Figure A1 in the appendix). These different 7 The estimated impulse responses of oil production and oil prices following the structural shocks are shown in Figure 2 in section 3.1 of the paper, when we discuss the changes in the dynamics of the oil market over time. 8 This finding is rather surprising given that PVR (2009) show that asymmetries in labor market characteristics are crucial to explain differences of the impact of oil supply shocks on consumer prices in individual Euro area countries.…”
Section: A Structural Var Modelmentioning
confidence: 99%
“…8 We find an impact on consumer prices which is relatively strong for all energy-importing countries except for Japan, whereas inflationary pressures are negligible or even negative in net energy-exporting countries (see also Figure A1 in the appendix). These different 7 The estimated impulse responses of oil production and oil prices following the structural shocks are shown in Figure 2 in section 3.1 of the paper, when we discuss the changes in the dynamics of the oil market over time. 8 This finding is rather surprising given that PVR (2009) show that asymmetries in labor market characteristics are crucial to explain differences of the impact of oil supply shocks on consumer prices in individual Euro area countries.…”
Section: A Structural Var Modelmentioning
confidence: 99%
“…Rodriguez and Sanchez (2009) applied both linear and nonlinear methodologies to the US, Germany, France, Italy, and the UK and found significant evidence of nonlinear effects of oil price shocks on real output and inflation. Cunado and Gracia (2003) investigated oil price shocks-macro economy relationship for many European countries for the period 1960-1999. They concluded that price shocks had permanent effects on inflation but only positive oil price shocks had negative short run influence on the industrial production.…”
Section: Literature Revi̇ewmentioning
confidence: 99%
“…12 The CPI index is used in order to deflate the oil price according to Ferderer (1996) and Cunado and de Gracia (2003) inter alia .…”
Section: Otherwisementioning
confidence: 99%